Uma proposta de formação continuada para o ensino com o texto/enunciado multissemiótico no ensino médio a partir do dispositivo da autoconfrontação - Freitas, Samya Semião (2022)
In this research, the aim is to analyze the perceptions of a group of Portuguese language teachers from public high schools about teaching with the multisemiotic text, with a view to proposing a Training Sequence (TS). For this, we carried out a study with High School Portuguese Lan-guage teachers. We took, as a corpus of analysis, the answers presented in an online question-naire and the transcription of the dialogues of the most significant sequences of the simple one, the cross self one and return to the collective. Furthermore, as a way of remembering and eval-uating the formative trajectory, in which the modules were decided by the collective of work, we also analyzed the production of seven biographiczines and two oral reports produced by the research participants. We resort to notions from the Dialogical Theory of Discourse (BAKH-TIN, 2011, 2014, 2015, 2018; VOLOCHINOV, 2017). The perspective of Multiliteracies is also adopted (ROJO; MOURA, 2012; ROJO; BARBOSA, 2015; ROJO; MOURA, 2019); and the prescribed, performed and actual work (CLOT, 2006), considering the prescribed dimension of the didactic material (AMIGUES, 2004) and of the official documents (PCN, 1998, 2000; PCN+, 2002; OCEM, 2006; BNCC, 2018; DCRC-CE, 2019, 2021). Teachers revealed percep-tions of students' difficulties in reading multisemiotic texts/utterances, such as retrieving con-textual references, and establishing dialogue and relationship between texts. Furthermore, in the teaching discourse, there is a tension between centrifugal forces, which tend towards the new, towards decentralization, such as the exploration of a broader notion of text and genres closer to the students; and centripetal forces, which tend towards the traditional, towards the standard, such as the privilege of the linguistic system to the detriment of the exploration of other essential semioses for the meaning effects of multisemiotic texts. We attest that, in addi-tion to stimulating the discussion about legitimate demands of the collective work, the proposed TS, based on the device of self-confrontation, encourages the appreciation of the teachers' ex-periences, reflection and the (re)creation of practice. We found that the teachers' perceptions about working with the multisemiotic text have an influence on the teaching action and, also, on the choices made by the teachers regarding the definition of the TS modules. Finally, we believe it is possible to (re)think the dynamics of teacher training based on a cyclical movement that starts with the flow of teachers' voices.